SLICE OF LIFE FORMULA IN JONAH HILL’S MID90S (2018) FILM - Rusmawan, Dendy Abyaz; Ropaidah, Anisa (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
Mid90s (2018), a film directed by Jonah Hill, masterfully employs a slice-of-life formula to depict the coming-of-age of Stevie, a thirteen-year-old in 1990s Los Angeles, abstracting the often-unspoken complexities of adolescence through a series of loosely connected, observational vignettes rather than a traditional linear narrative. The film eschews explicit plot points and grand dramatic arcs, instead immersing the viewer in the mundane yet formative experiences of Stevie's summer: the tentative steps into a new social group of older, rebellious skateboarders, the awkward fumbling with identity and belonging, the casual cruelty and genuine camaraderie within the group, and the subtle shifts in his relationship with his troubled home life. Through extended, unhurried scenes of skateboarding, loitering, and late-night conversations, the film captures the raw, unfiltered essence of youth, where moments of boredom, exhilaration, vulnerability, and fleeting independence coalesce to form the fragmented but deeply impactful mosaic of a boy finding his place in a chaotic world, allowing the audience to intuit the emotional and psychological shifts occurring beneath the surface of everyday interactions.